1997
DOI: 10.1161/01.cir.96.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Human Coronary Artery Composition by Raman Spectroscopy

Abstract: The chemical composition of coronary artery can be quantified accurately with Raman spectroscopy. This opens the possibility of using histochemical analysis to predict acute events such as plaque rupture, to follow the progression of disease, and to select appropriate therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
114
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 21 publications
1
114
0
Order By: Relevance
“…Details of the model and its validation with standard chemical assays have been described previously. 24,25 In calcified plaques, CS occupied a large part of the tissue volume examined by Raman spectroscopy. To obtain information about the remaining noncalcified tissue, we renormalized the chemical fractions in the NCR, eg,…”
Section: Selected Abbreviations and Acronymsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the model and its validation with standard chemical assays have been described previously. 24,25 In calcified plaques, CS occupied a large part of the tissue volume examined by Raman spectroscopy. To obtain information about the remaining noncalcified tissue, we renormalized the chemical fractions in the NCR, eg,…”
Section: Selected Abbreviations and Acronymsmentioning
confidence: 99%
“…19,20 Recently, we demonstrated that the chemical composition of human coronary artery can be quantified with NIR Raman spectroscopy. [21][22][23][24][25] Raman spectra were obtained from homogenized coronary artery samples and processed to calculate the relative weights (in percent) of FC, CE, TG, and PL, and CS in the examined volume of arterial tissue. These chemical weights agreed with those determined by standard lipid assays and CS assays to within a few percent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The point-to-point spatial variations in the structure of plaque samples reduce the accuracy of the Raman assay and its applicability for noninvasive quantitative analysis. 13,14 There is currently no …”
mentioning
confidence: 99%
“…The point-to-point spatial variations in the structure of plaque samples reduce the accuracy of the Raman assay and its applicability for noninvasive quantitative analysis. 13,14 There is currently no method available for the accurate quantification of liquid and liquid-crystalline phases of CEs in a plaque. The best method available, polarized light microscopy, can estimate the relative amounts of CE phases in a thin section (10 m) dissected from a plaque.…”
mentioning
confidence: 99%